PENGARUH GAME ONLINE ANDROID TERHADAP PRESTASI BELAJAR SISWA KELAS IV MI ISLAMIYAH KEBOMLATI KECAMATAN PLUMPANG KABUPATEN TUBAN TAHUN PELAJARAN 2017-2018 - Agus Fathoni Prasetyo; Dinna Shofia (PREMIERE : Journal of Islamic Elementary Education, 2019)
Progress in the field of communication technology in the current era of globalization is producing sophisticated media so as to facilitate the needs needed quickly. In the past few years the android online game play on smartphones has been very interested in most circles, especially students. The positive impact of online games is that the more difficult a game is, the more high levels of concentration are needed to improve hand and eye coordination, while the negative impact of this android online game is that students often forget about other activities and forget their assignments as students. This research was conducted with a quantitative approach. The form of this research is correlational. The subjects in this study were fourth grade students of MI Islamiyah Kebomlati, Plumpang Subdistrict, Tuban District, 2017/2018 Academic Year, with 18 students consisting of 8 male students and 10 female students. The use of android online games for grade IV MI Islamiyah Kebomlati students in Plumpang sub-district of Tuban in the 2017/2018 academic year is sufficient or moderate. Because the average value of 25.5. The effect of android online games on the learning achievement of fourth grade MI Islamiyah Kebomlati Districts Plumpang District of Tuban in the academic year 2017/2018 based on the results of research on interpretation using the t-table value r2 determinaation coefficient, it turns out that the t-count () is smaller than t-table, at the significance level of 5% (2,120). Thus there is an insignificant coefficient of determination between android online games and the learning achievement of fourth grade students of MI Islamiyah Kebomlati, Plumpang Subdistrict, Tuban Regency in the academic year 2017/2018. This shows that the android online game has no effect on student achievement IV MI Islamiyah Kebomlati Plumpang District of Tuban in the 2017/2018 academic year.